Menilik Hak Pekerja Di Masa Pandemi: Analisis Naratif Ulangan 24:14-15 - Joses Worthy de Poere (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
Data shows the huge impact of the pandemic on workers globally, including in Indonesia. Workers’ rights have directly become an issue along with companies and entrepreneurs who continue to suffer losses. A church that has a social responsibility should pay more attention to this. However, in reality, this is an issue that is rarely discussed. The social assistance provided to the community is mostly limited to ceremonial purposes in celebrating certain ecclesiastical celebrations. Moreover, the church rarely voices the rights of the economically oppressed people firmly. Therefore, this paper intends to contribute to theological thinking and advocacy for the issue of workers' rights during the pandemic. This theological thinking is built on the narrative analysis of Deuteronomy 24:14-15. This analysis is expected to be useful to remind us that concerns regarding workers' rights have existed since ancient times. Therefore, this analysis aims to provide an overview and an invitation to all parties, especially the church, to pay attention to this issue. In the end, the reflections of this paper will provide advocacy related to workers' rights during the pandemic that can be developed by readers. I hope that concerns regarding workers' rights during the pandemic can grow and become daily spirituality.